Gestão de imagens em movimento de matérias jornalísticas em banco de dados na TV Digital - Gonçalves, Maria Valéria Bertachini do Nascimento [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Due to the intense information flow, together with the techonological trends of control, storage and distribution, information management is considered as a key factor enabling dynamism and skills to manage and direct this raw material that is information. In this scenario, is the television media that uses mainly the image as information while determining language for the audiovisual sector. Television journalism the image appears to portray and cover your news. The study object of this thesis is the management of movement of news stories in images, considering that this information will reach its goal if it is processed and managed in the database, following a following and promoting the distribution and use of this information its users to quickly and accurately. The central question that guided the studies and research refers to the treatment of the moving image and how it should be guided so that there is accuracy in recovery. Thus, if the objective was, in general, the optimization in activities involving information management movement of news stories in pictures in a regional television station offer theoretical and practical contribution to provide management practices for this area Digital Television. The required specific objectives resulted in the construction of a theoretical framework to support that following culminated in conducting exploratory study by the Documentation Centre - CEDOC, the broadcaster TV TEM, affiliated to Rede Globo and brinding together the cities of Sorocaba, Bauru, São Jose do Rio Preto and Itapetininga, to present guiding parameters to the moving image management conduct with the databases in Digital TV ambience. The methodological procedures to achieve the established objectives were operationalized through the development of exploratory research, with the steps of the research/literature review; field research that split into information retrieval, enabling the characterization of TEM TV and CEDOC...

Devido ao fluxo informacional intenso, somado às tendências tecnológicas, de controle, armazenamento e distribuição, a gestão da informação é considerada como fator primordial possibilitando dinamismo e competências para gerir e direcionar essa matéria prima que é a informação. Nesse cenário, encontra-se a mídia televisiva que utiliza, principalmente, a imagem como informação, enquanto linguagem determinante para o setor audiovisual. No telejornalismo a imagem é apresentada para retratar e cobrir suas notícias. O objeto de estudo desta dissertação é a gestão de imagens em movimento de matérias jornalísticas, considerando-se que essa informação atingirá seu objetivo se a mesma for beneficiada e gerida no banco de dados, seguindo uma sequência e favorecendo a distribuição e uso desta informação a seus usuários de forma rápida e precisa. A questão central que norteou os estudos e pesquisa refere-se ao tratamento da imagem em movimento e como ela deverá pautar para que haja a precisão na recuperação. Assim, objetivou-se, de modo geral, a otimização nas atividades que envolvem a gestão da informação de imagens em movimento, de matérias jornalísticas em uma emissora regional de televisão e oferecer contribuição teórico-prático de modo a proporcionar condutas de gestão para essa área na Televisão Digital. Os objtivos específicos estipulados resultaram na construção de um referencial teórico de apoio, que na sequência culminou em realização de estudo exploratório junto ao Centro de Documentação - CEDOC, da emissora TV TEM, afiliada à Rede Globo e que congrega as cidades de Sorocaba, Bauru, São José do Rio Preto e Itapetininga, a fim de apresentar parâmetros norteadores às condutas de gestão de imagens em movimento junto aos bancos de dados em ambiência de TV Digital. Os procedimentos metodológicos para atingir os objetivos estabelecidos foram operacionalizados mediante o...
Keywords: Videoteipes - Administração; Jornalismo; Televisão digital; Arquivos audiovisuais; Materiais audiovisuais; Video tapes - Management